TURKISH PREP SCHOOL EFL STUDENTS’ BELIEFS ABOUT LANGUAGE LEARNING - Arslan, Gülçin; Kafes, Huseyin (International Online Journal of Education and Teaching, 2021)
This study investigates the relationship between Turkish EFL learners’ beliefs about language learning and learner features, such as gender, age, and language proficiency level. The study was conducted at Anadolu University, School of Foreign Languages, with the participation of 242 Turkish prep school EFL students with different levels of English proficiency in the spring semester of the 2018-2019 academic year. The data were collected using Horwitz’s inventory (1987), “Beliefs about Language Learning Inventory” (BALLI). The results of the study showed no significant relationship between the participants’ features, that is, gender, age, and language proficiency level and their beliefs about language learning. However, subtle relationships were discerned between the participants’ features and their beliefs about language learning. Considered in the light of the results of previous studies on the same issue, the results of our study suggest that the interplay between learner beliefs about language learning and learner features is dynamic, complex, and context-specific, which underline the importance of adopting a hands-on approach with individualized attention to the situation and a timely-intervention of students’ misplaced beliefs about language learning. Taking the results of previous studies into account, the results of this study are discussed and pedagogical implications are offered for stakeholders in language learning and teaching. Keywords: Turkish EFL learners, beliefs about language learning,